Tannin Loaded Nanoparticles and its Therapeutic Applications – A Comprehensive Review - Kumar, S. Sathesh (Asian Journal of Pharmaceutics (AJP), 2021)
Cancer is one stage of a condition that occurs due to uncontrolled growth of cells and is caused by many factors ranging from genetic mutations to different lifestyle factors such as exposure to chemicals, radiation, tobacco usage, and physical exercise so on. They are so many surgeries and therapies treatment is available for cancer but this treatment only reduces the symptoms of the disease, and complete cannot be expected. These chemical drugs are more prominent to destroy cancer cells in our body but they increase side effects includes nausea and vomiting it will lead to damage to the vital organs such as the kidney, heart, and lung. Phytoconstituents are one of the promising treatment prospects for minimizing the side effects and to improve effectiveness of the chemotherapeutic drugs and it is used for natural products, which have been traditionally used to treat many types of cancer. Many plant extracts were described that pharmacological activities are characteristic of their phytoconstituents includes tannins, flavonoids, saponin, alkaloids, and terpenes. Tannins are secondary metabolites of plants. Tannins are popularly known as natural polyphenolic molecules possess many pharmacological actions such as antibacterial, anti-cancer, antioxidant, chemo-preventive, and anti-inflammatory actions. One of the problems that present the use of tannins is their poor bioavailability. Nanoparticles have been introduced a different type of formulation and evaluation methods to identify their bioavailability of a drug. The present study concentrates on tannin-loaded nanoformulations to increase the bioavailability in the treatment of cancer.